2005
DOI: 10.1093/aje/kwi193
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Mortality among US Men and Women with Asthma and Hay Fever

Abstract: The relation between self-reported physician-diagnosed asthma and/or hay fever and cancer mortality was explored in a prospective cohort study of 1,102,247 US men and women who were cancer-free at baseline. During 18 years of follow-up, from 1982 to 2000, there were 81,114 cancer deaths. Cox proportional hazards models were used to obtain adjusted relative risks for all cancer mortality and for cancer mortality at 12 sites associated with allergy indicators. There were significant inverse associations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
166
3
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(185 citation statements)
references
References 44 publications
8
166
3
8
Order By: Relevance
“…According to a recent review on cancer risk in asthma (Turner et al, 2006), only one Finnish cohort study has shown a positive association (Vesterinen et al, 1993), but significant only for men. The number of cancer cases in our study was almost the sum of cases in three earlier cohort studies (Kallen et al, 1993;Vesterinen et al, 1993;Turner et al, 2005). For the cancers overall, the highest risks were noted during the first year after last hospital admission for asthma, which could be due to lead time bias because of concomitant diagnosis.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…According to a recent review on cancer risk in asthma (Turner et al, 2006), only one Finnish cohort study has shown a positive association (Vesterinen et al, 1993), but significant only for men. The number of cancer cases in our study was almost the sum of cases in three earlier cohort studies (Kallen et al, 1993;Vesterinen et al, 1993;Turner et al, 2005). For the cancers overall, the highest risks were noted during the first year after last hospital admission for asthma, which could be due to lead time bias because of concomitant diagnosis.…”
Section: Discussionmentioning
confidence: 40%
“…The increased risks in cancers of the colon, liver, and pancreas have not been reported earlier and most earlier studies have shown a reduced risk or risk close to unity (Vesterinen et al, 1993;Talbot-Smith et al, 2003;Turner et al, 2005). The excess of colon cancer increased with the number of hospital admissions and the SIR was 1.99 for those hospitalised more than 5 times, highest for any cancer, suggesting a true aetiological link.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[13][14][15][16][17][18] Risk differed between men and women, and depended on the type of allergy and cancer site. [14][15][16]19 In a cohort study by Soderberg et al (2004), there was at least a doubling of risk of certain types of leukemia among individuals with hives.…”
Section: Allergies and Cancer Riskmentioning
confidence: 99%
“…A Swedish register-based cohort study, which included younger and older participants (median age of 30 and 54 years, respectively), found that glioma and meningioma increased risks of the younger and decreased risks of the older age group (10). A further register-based retrospective cohort study reported a positive association between atopic dermatitis and all brain tumours (11), whereas other cohort studies showed no association with allergies (12,13).…”
mentioning
confidence: 99%